Single-cell transcriptomic analysis reveals epithelial and microenvironmental heterogeneity in small cell carcinoma of the esophagus - Yin, Xiaolei; Li, Xiaopeng; Mi, Lili; Hou, Jiaojiao; Yin, Fei (Frontiers in Immunology, 2025)
BackgroundSmall cell carcinoma of the esophagus (SCCE) is a rare and highly aggressive malignancy with limited therapeutic options and poor prognosis. The paucity of clinical specimens and lack of established experimental models have hindered a comprehensive understanding of its cellular heterogeneity and tumor microenvironment.MethodsWe performed single-cell RNA sequencing on SCCE samples, and integrated them with publicly available scRNA-seq datasets from esophageal squamous cell carcinoma (ESCC), esophageal adenocarcinoma (EAC), and adjacent normal tissues (NT) from ESCC and EAC cases. An integrative transcriptomic analysis was conducted to identify cell types, infer malignant states, reconstruct differentiation trajectories, evaluate immune landscapes, and investigate fibroblast subtypes and cell–cell communication networks.ResultsSCCE tumors were characterized by a predominance of malignant epithelial cells and exhibited a profoundly immunosuppressed phenotype, with reduced immune infiltration and widespread downregulation of immune checkpoint genes. Malignant epithelial cells showed pronounced chromosomal instability and were classified into three transcriptionally distinct subtypes with divergent differentiation trajectories. The tumor microenvironment featured a complex stromal compartment, with enrichment of extracellular matrix fibroblasts (eCAFs) characterized by elevated ELF3 regulatory activity, and collagen-driven signaling predominantly mediated by inflammatory CAFs (iCAFs). SCCE also showed the most intricate cell–cell communication network among esophageal cancer subtypes.ConclusionOur single-cell atlas offers a detailed view of the cellular heterogeneity and microenvironmental complexity of SCCE, highlighting its distinct tumor architecture, immune exclusion, and stromal reprogramming. These findings provide a valuable resource for understanding SCCE biology and form a basis for future mechanistic and exploratory biological investigations.